Social network in the 2015 dreams of a male dreamer - Schredl, Michael; Schweickert, Richard (International journal of dream research, 2022)
Social interactions play an important role in dreams and, thus, the question arises whether the characteristics of the dream social network based on co-occurrence of persons within dreams is comparable with the characteristics of waking-life social networks. The present analysis included 696 dreams reported by a male dreamer in the course of one year. Overall, the findings support the notion that a dream social network shows the characteristics of a small world network (small average distances, high clustering), and the power low distribution of co-occurrences - similar to waking-life social networks. The clustering was most obvious for the core family members of the dreamer; they are more likely to co-occur than occur with persons of other social areas. More studies are needed to link inter-individual differences within the properties of the dream social network to differences in the current and former waking-life social networks of the dreamer.